Story of rational approximation for the class of Stiltjes functions: from Stiltjes to recent optimal estimations of errors - Gilewicz, J. (Український математичний журнал, 1994)
The history of obtaining inequalities for Pade approximant error in the Stieltjes case is given. Inequalities optimal with respect to the order are obtained for these approximants by using results of J. Vinuesa and A. P. Magnus. Наведено історію встановлення нерівностей для похибок апроксимацій Паде у стільєсівському випадку. Доведено оптимальні за порядком нерівностей для цих апроксимацій з використаннням результатів Вінуеса та Магнуса.